Gambaran tingkat pengetahuan kader tentang buku KIA di Posyandu wilayah Kelurahan Demangan Kecamatan Gondokusuman Kota Yogyakarta tahun 2015 - Vitia Eka Prahastuti; Suherni Suherni; Dwiana Estiwidani (Jurnal Kesehatan Ibu dan Anak, 2016)
The status of child nutrition still be problems, hence the effort to early detection of malnutrition important to do.The role of cadres very influential as an effort early detection of malnutrition is by using mch book. Knowledge isone factor affecting cadres in the utilization mch book. This research aims to understand the level of knowledgeabout the book cadres mch. The research is descriptive research using the approach of cross-sectional with thesubject of research cadres demangan village area in the city of Yogyakarta gondokusuman as many as 58people, an instrument of this research using questionnaire, data analyzed by univariabel. Results of thisresearch: (l)Characteristics Demangan cadres village area has the largest proportion of cadres on the age of20-50 years old, education at the secondary level, did not work, and has become cadres for >10 years; (2)thelevel of knowledge about understanding cadres mch book, the functions and benefits mch book, uses mchbook, the assessment of achart weigh mch inthe book and the follow-up to the result of weighing the majority ofknowledgeable good; (3) a level cadres knowledge about how to fill KMS mch in the and early detection ofmalnutrition with mch book the majority of knowledgeable enough. The level of knowledge about the bookcadres mch good the majorityof affected byage, education, work, and old workings.